Analysis of The Supporting Capacity of The Stake Foundation on Soekarno Hatta Airport Accessibility Project - Resi Aseanto Aseanto; Muhammad Wira Kaloka (NAROTAMA UNIVERSITY, Indonesia, 2021)
The construction of a foundation is very large function in a construction. In general the foundation is defined as an underground building that passes on the load derived from the weight of the building itself and the outer load that works on the building to the surrounding land. The foundation of the stake is a relatively long and slim rod that is used to channel the foundation load through the soil layer with a low support capacity of hard soil layer that has a high carrying capacity that is relatively deep compared to the shallow foundation. The carrying capacity of the stake is derived from the end bearing capacity obtained from the pressure of the end of the pole and the friction bearing capacity obtained from the carrying capacity of the friction or adhesion force between the stake and the surrounding soil. This research uses an analytical research method in which in the calculation of the planning of the foundation of the stake using the calculation of the capacity of carrying capacity with the method of bagemann and mayerhoff. From the calculation of vertical style carrying capacity based on sondir data using bagemann method at the first stake point of 1059.50 kN and at the second point of 1015.95 kN, and the result of SPT data using mayerhoff method at the first stake point of 663.88 kN and at the second point of 498.76 kN. Qultimate single pole horizontal carrying capacity calculation of 216 kN, Single Qizin amounted to 72 kN, Group of 228 kN.The result of the calculation of vertical carrying capacity of the group stake is 734.1732 kN.The result of the calculation of tuggal pole reduction is 11.62 mm, The stake group is 10.77 mm, so the calculation result for the drop of a single pole is smaller than the permit drop which is smaller than 100mm.